Expression of CCR3 and CCR4 Suggests a Poor Prognosis in Mycosis Fungoides and Sézary Syndrome - Yuki Shono; Hiraku Suga; Hiroaki Kamijo; Hikari Fujii; Tomonori Oka; Tomomitsu Miyagaki; Naomi Shishido-Takahashi; Makoto Sugaya; Shinichi Sato (Medical Journals Sweden, 2019)
Tumor cells in cutaneous T-cell lymphoma express limited numbers of chemokine receptors. We investigated the expression patterns of CXCR3, CCR3, CCR4 and CCR10 in mycosis fungoides, Sézary syndrome, lymphomatoid papulosis and anaplastic large cell lymphoma in 121 skin biopsy samples. CXCR3 was expressed in 86% of mycosis fungoides cases but in no anaplastic large cell lymphoma cases. CCR3 was expressed in 73% of cases of CD30+ lymphoproliferative disorders such as lymphomatoid papulosis and anaplastic large cell lymphoma. Mycosis fungoides/Sézary syndrome patients with high CCR3 or CCR4 expression had a poorer survival prognosis than mycosis fungoides/Sézary syndrome patients whose tumor cells did not express these receptors. CCR10 was expressed in 50% of mycosis fungoides/Sézary syndrome cases and in 13% of cases with CD30+ lymphoproliferative disorders. These results suggest that differential patterns of CXCR3, CCR3, CCR4 and CCR10 expression are useful for the diagnosis of cutaneous T-cell lymphoma. Moreover, expression of CCR3 or CCR4 suggests a poor prognosis in mycosis fungoides/Sézary syndrome.